Heterorhabditis floridensis n. sp. (Rhabditida: Heterorhabditidae) from Florida - Nguyen, Khuong B.; Gozel, Ugur; K_Ppenh_Fer, Heather S.; Adams, Byron J. (Zootaxa, 2006)
In a survey of entomopathogenic nematodes associated with plants and trees in areas adjacent to production citrus groves in Florida, a new species of nematode in the genus Heterorhabditis was found based of morphological and molecular studies. The new nematode is described as Heterorhabditis floridensis n. sp. H. floridensis n. sp. is characterized by males, females, and infective juveniles. For males, the number of papillae in the terminal group of bursa is variable, either with 2 pairs of papillae (40%), with 3 papillae on one side and 2 papillae on the other side (30%), with one pair of papillae (20%), or with three pairs of papillae (10%). SW and GS values are 179 and 50, respectively. Females have a typical vulva pattern, which is different from that of closely related nematode species H. bacteriophora, H. mexicana, and H. indica. For infective juveniles, EP=109 (101–122) µ m, ES=135 (123–142) µ m, tail length=103 (91–113) µ m, and a=27.6 (25–32) are different from those of the above-mentioned three related nematodes. Phylogenetic analysis based on ITS regions show that the new species forms a clade with H. mexicana, H. baujardi and H. indica and differs from these species by several nucleotide autapomorphies.